Color-induced changes in Chrysanthemum morifolium: an integrative transcriptomic and metabolomic analysis of petals and non-petals - Wei, Jianhong; Zeng, Zhaoxiang; Song, Chengwu; Lv, Qing; Chen, Guangya; Mo, Guoyan; Gong, Ling; Jin, Shuna; Huang, Rongzeng; Huang, Bisheng (Frontiers in Plant Science, 2024)
Chrysanthemum morifolium (CM), renowned for its diverse and vibrant varieties, holds significant ornamental and medicinal value. Despite this, the core regulatory mechanisms underlying its coloration, especially in non-petal tissues (i.e., the parts of CM that do not include petals, such as the reproductive tissues, receptacle and calyx), have been insufficiently studied. In this study, we performed transcriptomic and metabolomic analyses on yellow, gold, and white CM petals, as well as non-petal tissues, to investigate the molecular processes driving color variation. A total of 90 differential metabolites were identified, with flavonoids, their derivatives, and lipids emerging as the predominant components of the metabolic profile. At the transcriptional level, 38 pathways were significantly enriched based on the expression of differential genes. The combined metabolomic and transcriptomic analyses revealed that glycerophospholipid metabolism, primarily involving lipids, served as a key regulatory pathway for both petal and non-petal parts across different tissue colors. Notably, white CM exhibited marked differences from their gold and yellow counterparts at both the metabolic and transcriptional levels. These findings offer critical insights into the molecular mechanisms governing CM coloration and provide a foundation for optimizing future breeding efforts.